Pediatric pneumonia – A clinico-pathological study - Pragati A. Sathe; Monalisa Dash; Pradeep Vaideeswar; Sunil Karande; Lamk Kadiyani (Indian Journal of Pathology and Microbiology)
Context: Numerous pathogens (bacteria, viruses, or fungi) can cause childhood pneumonia. The clinical presentations of viral and bacterial pneumonia can be similar. Though viruses are a more common cause as compared to bacteria, antibiotics remain the first line of treatment for pneumonia. Aims: This study was planned to describe the pulmonary histopathological patterns in cases of pediatric pneumonia (age <12 years) at autopsy and aimed to identify the probable etiology and correlate with clinical presentations. Materials and Methods: This is a single-center 3-year retrospective descriptive autopsy study. Relevant clinical data was correlated with the postmortem findings. The cases were assigned to one of the following categories based on probable etiology: viral, bacterial, mixed, or others. Results: There were 89 cases with a postmortem diagnosis of pneumonia among 262 autopsied children (34%). Most patients had histological patterns that suggested viral and bacterial etiology in 46 (51.7%) and 27 (30.3%), respectively. A total of 35 out of 46 patients received antibiotics. Twelve cases had mixed viral and bacterial patterns. Antibiotics were also given in the remaining four children (4.5%) with a similar clinical presentation, where a diagnosis of tuberculosis (03 cases) and invasive aspergillosis (01) was made at autopsy. Conclusion: Neither clinical features nor investigations reliably differentiate between viral and bacterial pneumonia. Autopsy has an important role in providing insights into the pathogenesis of pneumonia and suggests inappropriate antibiotic exposure. No prior Indian studies have been performed to compare the clinical and postmortem findings of pneumonia in children.